(untitled) (Journal of Hama University, 2024)
This study aims to find out the macroscopic and histological changes resulting from the administration of high doses of ivermectin in the liver of domestic rabbits, the study was conducted on (32) adult rabbits, the rabbits were divided into four groups and injected under the skin ivermectin and the witness groups injected distilled water, and the groups were given a dose every week for up to four weeks and blood samples were taken for biochemical the results of the biochemical study showed a significant increase (p<0.05 in the level of ( ALT-AST) in the blood plasma when injected with ivermectin preparation at a high dose compared to the witness Group, and it turns out that the larger the dose size and number, the higher the level of enzymes in the blood plasma .The results of the study showed the presence of obvious changes in the liver tissue represented by the pigmentation of the nuclei in dark blue, which indicates the condensation of chromatin in the hepatic cells, the presence of protein and vacuolar degeneration in the hepatic cells and necrosis, the presence of inflammatory infiltration and expansion of some blood vessels was observed,.